Convergent synthesis of diversified reversible network leads to liquid metal-containing conductive hydrogel adhesives - Yong Xu (Nature Portfolio, 2021)
The need for multifunctional materials for tissue engineering applications requires the development of multicomponent systems. Here, the authors report on the creation of a liquid metal-containing hydrogel with multiple covalent and noncovalent bonds to produce a tailorable, biocompatible biomaterial.